KOMPARASI ENERGI SURYA DENGAN LAMPU HALOGEN TERHADAP EFISIENSI MODUL PHOTOVOLTAIC TIPE MULTICRYSTALLINE - Asrul, Asrul; Demak, Reyhan Kyai; Hatib, Rustan (Jurnal MEKANIKAL, 2016)
Abstract: Comparison between solar energy and halogen lights on efficiency of photovoltaic multicrystalline module. From various studies previously showed that the difference in the efficiency of the solar cells to the effects of the intensity and temperature of the surface of solar panels on the various types of solar cells. This study discusses the effect of temperature on the type Multicrystalline solar panel efficiency by using a simulation of light as a substitute source of the sun. The test is performed measurements of the parameters used to analyze the effect of light on the efficiency of solar panels. The results were obtained value of the highest efficiency at light power of 300 watts at 2.19% at the panel surface temperature of 31,3 0C, then 500 Watt lamp at a temperature of 2.13% and the latter 33,6 0C 1000 Watt lamp with efficiency values of 2.06% on the panel surface temperature of 34,5 0C.